HUBUNGAN TEKNIK MENYUSUI DENGAN KELANCARAN PRODUKSI ASI PADA IBU MENYUSUI DI DERMAWATI MEDAN - Suyanti Suwardi; Ivansri Marsaulina; Novy Ramini Harahap; Yuliana Yuliana (Indonesian Trust Health Journal, 2023)
Breastmilk is the only baby's best food for up to six months because it has a nutritional composition for baby's growth and development. According to WHO in 2016 there were 40% of infants aged 0-6 months given exclusive breastfeeding. The aim of this research is to know the relationship of breastfeeding techniques with the smothness of breastmilk production on nursing mothers at Dermawati Medan. The type of this research is analytical survey research method with cross sectional approach. This research was conducted at Dermawati Clinic from July to September 2022. The populations in the study were breastfeeding mothers as many as 43 people. The samples of the study were 32 people with accidental sampling techniques. The data analysis used univariate and bivariate analysis and tested by using chi square test (sig-α 0,05). Based on the chi-square statistical test results obtained p-value value of 0.002 <sig α (0.05), means that there was a significant relationship between breastfeeding techniques and smoothness of Breasmilk production. The conclusion of this study shows that there is a relationship between breastfeeding techniques and the smoothness of breastmilk on nursing mothers at Deremawati Clinic Medan. It is suggested that the results of this study are expected to add insight and knowledge of mothers who are breastfeeding about the relationship of breastfeeding techniques with the smoothness of breastmilk production. Abstrak ASI merupakan satu-satunya makanan terbaik bayi sampai enam bulan karena mempunyai komposisi gizi untuk pertumbuhan dan perkembangan bayi. Menurut WHO tahun 2016, terdapat 40% bayi berusia 0-6 bulan diberikan ASI eksklusif. Tujuan penelitian ini Untuk Mengetahui Hubungan Teknik Menyusui dengan Kelancaran produksi ASI pada Ibu Menyusui di Klinik Dermawati Medan. Jenis penelitian yang digunakan adalah metode penelitian survei analitik dengan pendekatan cross sectional. Penelitian ini dilakukan di Klinik Dermawati, dari bulan Juli sampai September 2022. Populasi dalam penelitian adalah ibu yang menyusui yaitu 43 orang, sampel penelitian berjumlah 32 orang dengan teknik sampling accidental. Analisa data yang digunakan adalah analisa univariat dan bivariat dengan menggunakan uji chi square (sig-α 0,05). Berdasarkan hasil uji statistik chi-square diperoleh hasil nilai p-value sebesar 0,002 < sig α (0,05), artinya ada hubungan yang signifikan antara teknik menyusui dengan kelancaran produki ASI. Kesimpulan dalam penelitian ini ada hubungan Teknik Menyusui Dengan Kelancaran produksi Pada Ibu Menyusui di Klinik Dermawati Medan. Disarankan hasil penelitian ini diharapkan dapat menambah wawasan dan ilmu pengetahuan ibu yang menyusui tentang hubungan teknik menyusui dengan kelancaran produksi ASI.